(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Vitamin A is considered as one of the essential micronutrients which are extensively associated with chemopreventive and therapeutic modalities. Carcinogenesis is a complex disease where environmental and genetic factors act as a predisposing cause bringing about alterations in the overall cell microstructure. Possible role of Retinoid, which is a form of Vitamin A, has been recognized in suppressing breast cancer, lung carcinoma, cancer of the colon, prostate cancer, blood cancers and to some extent the cancers of the oral cavity. Retinoid is known to act through RAR/RXR receptors to form ligands and thereby affect the transcription process and controls angiogenesis, abnormal proliferation, and metastasis. Some varieties of leukemia have shown better results with Retinoid therapy. However its role in oral premalignant and malignant lesions are not much known. This review discusses the physiologic, epigenetic and molecular role of Retinoids in lesions of the oral cavity.